Induction Strategies in Lung Transplantation: Alemtuzumab vs. Basiliximab a Single-Center Experience - Furukawa, Masashi; Chan, Ernest G.; Ryan, John P.; Hyzny, Eric J.; Sacha, Lauren M.; Coster, Jenalee N.; Pilewski, Joseph M.; Lendermon, Elizabeth A.; Kilaru, Silpa D.; McDyer, John F.; Sanchez, Pablo G. (Frontiers in Immunology, 2022)
Background: Induction therapy is used in about 80% of lung transplant centers and is increasing globally. Currently, there are no standards or guidelines for the use of induction therapy. At our institution, we have two induction strategies, basiliximab, and alemtuzumab. The goal of this manuscript is to share our experience and practice since this is an area of controversy. Methods: We retrospectively reviewed 807 lung transplants performed at our institution between 2011 and 2020. Indications for the use of the basiliximab protocol were as follows: patients over the age of 70 years, history of cancer, hepatitis C virus or human immunodeficiency virus infection history, and cytomegalovirus or Epstein-Barr virus (donor positive/ recipient negative). In the absence of these clinical factors, the alemtuzumab protocol was used. Results: 453 patients underwent alemtuzumab induction and 354 patients underwent basiliximab. There were significant differences in delayed chest closure (24.7% alemtuzumab vs 31.4% basiliximab, p = 0.037), grade 3 primary graft dysfunction observed within 72 hours (19.9% alemtuzumab vs 29.9% basiliximab, p = 0.002), postoperative hepatic dysfunction (8.8% alemtuzumab vs 14.7% basiliximab, p = 0.009), acute cellular rejection in first year (39.1% alemtuzumab vs 53.4% basiliximab, p < 0.001). The overall survival rate of the patients with alemtuzumab induction was significantly higher than those of the patients with basiliximab induction (5 years survival rate: 64.1% alemtuzumab vs 52.3%, basiliximab, p < 0.001). Multivariate Cox regression analysis confirmed lower 5-year survival for basiliximab induction (HR = 1.41, p = 0.02), recipient cytomegalovirus positive (HR = 1.49, p = 0.01), postoperative hepatic dysfunction (HR = 2.20, p < 0.001), and acute kidney injury requiring renal replacement therapy (HR = 2.27, p < 0.001). Conclusions: In this single center retrospective review, there was a significant difference in survival rates between induction strategies. This outcome may be attributable to differences in recipient characteristics between the groups. However, the Alemtuzumab group experienced less episodes of acute cellular rejection within the first year.